2006
DOI: 10.1016/j.crhy.2006.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Dew nucleation and growth

Abstract: Dew is the condensation of water vapor into liquid droplets on a substrate. It is characterized by an initial heterogeneous nucleation on a substrate and a further growth of droplets. The presence of a substrate that geometrically constrains the growth is the origin of the peculiarities and richness of the phenomenon. A key point is the drop interaction through drop fusion or coalescence, which leads to scaling in the growth and gives universality to the process. As a matter of fact, growth dynamics are only d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
206
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(220 citation statements)
references
References 41 publications
12
206
0
2
Order By: Relevance
“…They found that the drop radius of the individual isolated droplets grows according a power law with exponent 1/3 except for PP surface similar to previous reports. [48][49][50][51]58 Growth rate of a single droplet surrounded by other droplets was found 14%-40% lower than that of a single isolated droplet because of the barrier effect to lateral vapor diffusion. 63 In a further study, Ucar and Erbil investigated the dropwise condensation rate of water breath figures on polyolefin polymer surfaces whose surface free energies were in a close range of 30-37 mJ/m 2 but having different surface roughness and CAH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the drop radius of the individual isolated droplets grows according a power law with exponent 1/3 except for PP surface similar to previous reports. [48][49][50][51]58 Growth rate of a single droplet surrounded by other droplets was found 14%-40% lower than that of a single isolated droplet because of the barrier effect to lateral vapor diffusion. 63 In a further study, Ucar and Erbil investigated the dropwise condensation rate of water breath figures on polyolefin polymer surfaces whose surface free energies were in a close range of 30-37 mJ/m 2 but having different surface roughness and CAH.…”
mentioning
confidence: 99%
“…In many experimental studies, water vapor at a specific humidity was sent onto cool surfaces resulting in rapid condensation. [49][50][51]53,58,61,62,65 On the other hand, condensation of water vapor from ambient air (without sending vapor to cool surfaces) was also studied. 59,63,64 Many studies also investigated the growth dynamics of condensed droplets applying theoretical models and simulation.…”
mentioning
confidence: 99%
“…While this mode which is known as filmwise condensation 14 ( Figure 1a) is quite common, the formation of a liquid film is not desired due to the large resistance to heat transfer. Meanwhile, if a surface is coated with a low-energy non-wetting 'promoter' material (i.e., long chain fatty acid, wax, polymer coating, self-assembled monolayer) [15][16][17][18][19] , or if it naturally adsorbs hydrocarbons and impurities on its surface from the surroundings (as in the case of gold, silver, and chromium) [20][21][22] , the vapor forms discrete liquid droplets ranging in size from microns to millimeters [23][24][25] . This process is known as dropwise condensation 26 ( Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming for simplicity that the drops lie on a squared lattice, this particular value of surface coverage corresponds to an average distance between the droplet interfaces of ≈ 0.8 R . At this point, we measure an average droplet radius of ≈ 10 µ m. Note that the relation between the contact angle, θ, and surface coverage: θ(deg) ≈ 200(1 − 2 ) indicates that there is no significant change in contact angle with temperature [10,11]. A metastable state of supercooled droplets grown by vapor condensation on the substrate is first reached.…”
mentioning
confidence: 99%